Gamification, Motivation, and Performance in Education: A Systematic Review - Prieto-Andreu, Joel Manuel (2022)
Introduction. The purpose of this review is to review the literature that analyzes the relationship between gamification, motivation, and learning and thus, provide pedagogical and didactic ideas for its implementation in non-university education. Method. A mixed methodology is applied, through which an intentional sample of 37 articles is analyzed, intentionally chosen following the evaluation standards of the AERA (2006), out of a total of 1,706 studies published in ISI Web Of Science. Results. Based on the AERA (2006) evaluation controls, 37 intentionally chosen studies were selected and analyzed. Gamification was confirmed as having a direct and positive impact on students’ experiences in terms of their motivation and performance. Discussion. The work points to gamification is being approached academically from two perspectives, as a methodology oriented to students’ motivation in their competence learning; and as a way to enhance academic performance in different areas of knowledge.